The Effect of Virtual Reality on the Pain Intensity of Postoperative Laparotomy Patients - Imam Subiyanto; Dhea Setya Nuraini (STIKes RSPAD RSPAD Gatot Soebroto, 2026)
Laparatomy is a surgical procedure that cuts through the abdominal wall to obtain problematic abdominal organs. Laparatomy surgery causes acute pain that can affect sleep quality, disturb patient comfort, and can cause patients to stay longer in the hospital. The purpose of this study was to determine the effect of virtual reality on the pain intensity of patients after laparatomy surgery. This study used a Pre Experimental research design with a One Group Pre Test - Post Test Design. Data collection was carried out by performing virtual reality interventions. With the number of respondents 10 patients using total sampling. The data obtained was then statistically processed using the Wilcoxon test. Statistical analysis with the Wilcoxon test resulted in a p value of 0.003 <0.05, indicating a significant effect of virtual reality therapy in reducing pain intensity in patients. Virtual reality is effective in reducing the pain intensity of patients after laparatomy surgery and is expected to be applied in hospitals to improve the quality of service in hospitals. Future researchers can apply to other types of surgery to see if the effect of virtual reality is consistent in various types of postoperative with a bigger sample.